Pelatihan Pendampingan Siswa Berkebutuhan Khusus Bagi Guru SD Pertiwi Makassar - Jafar, Eka Sufartianinsih; Ansar, Wilda; Bungawali, Andi Nahliah; Wahyuni, Andi Fitri (IPTEK: Jurnal Hasil Pengabdian kepada Masyarakat, 2024)
Abstract. This Community Service activity is carried out at SD Pertiwi Makassar which is an inclusive school, almost every class has students with special needs. Pertiwi Makassar Elementary School has obstacles in assisting students with special needs, ranging from knowledge, special assistants, to supporting facilities (facilities and infrastructure) for students with special needs. So far, not all students with special needs have Special Accompanying Teachers (GPK), so more students with special needs are only accompanied by class teachers during learning. This program aims to enable teachers to recognize and understand how to assist students with special needs, so that teachers can assist students with special needs with assistance that suits the needs and conditions of students. The provision of psychoeducation in the form of assistance training for students with special needs can increase the understanding and knowledge of teachers to be able to assist students with special needs with assistance that suits their needs that are different from regular student.